2019
DOI: 10.1097/md.0000000000014758
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-based paclitaxel or nab-paclitaxel for heavily treated relapsed/refractory small cell lung cancer

Abstract: Treatment options for patients with relapsed/refractory small cell lung cancer (R/R SCLC) are limited, and the efficacy of salvage therapies for heavily treated patients should be assessed. Here, we evaluated the efficacy of paclitaxel (PTX) in R/R SCLC patients.A single-institute retrospective chart review was conducted. The primary endpoint was overall survival (OS), whereas the secondary endpoints were progression-free survival (PFS), overall response rate, disease control rate (DCR), and safety.Thirty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Similarly, a retrospective analysis reported outcome of 31 heavily pre-treated Japanese SCLC patients of whom only 4 received nab-paclitaxel, preventing any meaningful consideration on the efficacy of this agent. 20 In our study, the discordance in terms of ORR between local and central assessment has been mainly due, at least in some cases, to an improper application of RECIST v1.1 by local radiologists. For example, two refractory patients considered as stable were reclassified as responders after central radiological review because of a misleading interpretation of two target liver lesions in one case and two pathological mediastinal lymph nodes in the other one.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, a retrospective analysis reported outcome of 31 heavily pre-treated Japanese SCLC patients of whom only 4 received nab-paclitaxel, preventing any meaningful consideration on the efficacy of this agent. 20 In our study, the discordance in terms of ORR between local and central assessment has been mainly due, at least in some cases, to an improper application of RECIST v1.1 by local radiologists. For example, two refractory patients considered as stable were reclassified as responders after central radiological review because of a misleading interpretation of two target liver lesions in one case and two pathological mediastinal lymph nodes in the other one.…”
Section: Discussionmentioning
confidence: 58%
“…Three Asian retrospective analyses conducted in relapsed SCLC patients showed some anti-cancer activity of nab-paclitaxel. [18][19][20] Since nab-paclitaxel has not been prospectively studied in relapsed SCLC yet, we designed this open-label, prospective Phase 2 trial with the aim to assess its activity and safety in patients with both refractory and sensitive disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, it responded to the nab-paclitaxel-containing regimen. There have been several reports of paclitaxel or nab-paclitaxel showing antitumor activity against SCLC (15,16). In the present case, nab-paclitaxel may have contributed to the therapeutic effect, as it is unlikely that continuous use of carboplatin or the switch from atezolizumab to pembrolizumab resulted in the marked antitumor effect.…”
Section: Discussionmentioning
confidence: 60%
“…Nab‐paclitaxel is generally recognized as a relatively mild chemotherapeutic agent with good tolerability compared with other chemotherapy regimens in various solid tumors, including NSCLC . Clinical trials showed that nab‐paclitaxel had better efficacy and safety than sb‐paclitaxel …”
Section: Discussionmentioning
confidence: 99%
“…The multivariable analyses showed that ECOG performance status of 1 (vs. 2) and age of 70–74 years (vs. 65–69) were independently associated with longer OS, while early treatment line of nab‐paclitaxel (first‐line vs. second‐line, first‐line vs. third‐ or further‐line) and age of 70–74 years (vs. 65–69) were independently associated with longer PFS. Sugiyama et al . identified the performance status and high lactate dehydrogenase levels as the independent predictors of poor OS in patients with refractory/relapsed NSCLC treated with nab‐paclitaxel.…”
Section: Discussionmentioning
confidence: 99%